2014
DOI: 10.1093/fampra/cmu081
|View full text |Cite
|
Sign up to set email alerts
|

Exploring GPs’ experiences of using diagnostic tools for cancer: a qualitative study in primary care

Abstract: Findings suggest that the embedding of clinical decision support tools into clinical practice is more likely to be achieved when they are perceived to support but not supersede the clinical judgement of their users. This element of our findings is a focal point of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 15 publications
6
37
0
1
Order By: Relevance
“…The reason for this could be that the GPs’ awareness of potential cancer symptoms and attitude towards urgent cancer referral changed through the CME-M. Similar results have also been found in qualitative studies about the use of RATs [44, 45] and in our previous analysis of the impact of the CME-M on GP knowledge, attitude and intentions [18]. …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The reason for this could be that the GPs’ awareness of potential cancer symptoms and attitude towards urgent cancer referral changed through the CME-M. Similar results have also been found in qualitative studies about the use of RATs [44, 45] and in our previous analysis of the impact of the CME-M on GP knowledge, attitude and intentions [18]. …”
Section: Discussionsupporting
confidence: 79%
“…Our intervention was developed on the basis of theoretical frameworks and reviews of empirical results to ensure optimal likelihood of positive effect [44–47]. The CME-M consisted of a variety of elements [18], and we could not validly identify the most effective parts of the CME-M; this calls for further research in changing the GPs’ behaviour [46].…”
Section: Discussionmentioning
confidence: 99%
“…Green et al reported further qualitative results from a subgroup of the Hamilton study, 21 showing that the majority of GPs reported finding the tool useful in consultations, heightening their awareness of potential cancer symptoms, reminding them of potential cancer risks, and affecting their referral thresholds, although not all of the participating GPs found the tool a valuable addition to their practice. 22 Similar results were reported by Dikomitis et al; a qualitative study that examined 23 GPs' experiences of using an electronic version of the tool (one for smokers and one for non-smokers) in addition to their practices' clinical software package. 23 The GPs in the study by Dikomitis et al reported that the tool raised their awareness of the potential for cancer as the cause of the symptoms, and that their referral rates were affected to varying degrees, but the authors of the study undertook no quantitative measurements of actual impact; for example, referral rates, new cancers diagnosed, or stage of new cancers diagnosed.…”
Section: Data Collection and Analysissupporting
confidence: 76%
“…However, our study has also shown that only people presenting with shorter histories of rectal bleeding are investigated promptly, and that healthcare professionals should remain alert to symptoms of possible CRC in people with a history of gastro-intestinal or mental health conditions. The increasingly widespread use of clinical decision support in primary care can also be informed by our findings (Dikomitis et al , 2015; Green et al , 2015), but further research is needed, alongside GPs and specialists, to identify mechanisms by which patients can be identified, referred and diagnosed in the most timely and appropriate way.…”
Section: Discussionmentioning
confidence: 78%